2020
DOI: 10.1186/s12940-020-00682-y
|View full text |Cite
|
Sign up to set email alerts
|

Preconception air pollution exposure and glucose tolerance in healthy pregnant women in a middle-income country

Abstract: Background Preconception exposure to air pollution has been associated with glucose tolerance during pregnancy. However, the evidence in low and middle-income countries (LMICs) is under debate yet. Therefore, this study aimed to assess the relationship between exposure to ambient particulate matter (PM) and traffic indicators with glucose tolerance in healthy pregnant women in Sabzevar, Iran (2019). Methods Two-hundred and fifty healthy pregnant wo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Air pollution exposure during pregnancy may also affect the development of GDM by similar mechanisms ( Ben-Haroush et al, 2004 ). The emerging evidence indicates that higher preconception exposure to air pollution might be associated with elevated blood glucose levels associated with increased insulin resistance and GDM development ( Najafi et al, 2020 ). An increasing number of epidemiological studies have examined the relationship between air pollution exposure and the risk of GDM ( Choe et al, 2019 ; Choe et al, 2018 ; Fleisch et al, 2014 ; Fleisch et al, 2016 ; Hu et al, 2015 ; Jo et al, 2019b ; Malmqvist et al, 2013 ; Padula et al, 2019 ; Pan et al, 2017 ; Pedersen et al, 2017 ; Robledo et al, 2015 ; Shen et al, 2017 ; Yu et al, 2020 ; Zhang, et al, 2020a ; Zheng et al, 2020 ), although conclusions are inconsistent regarding the effects of different air pollutants and exposure windows.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution exposure during pregnancy may also affect the development of GDM by similar mechanisms ( Ben-Haroush et al, 2004 ). The emerging evidence indicates that higher preconception exposure to air pollution might be associated with elevated blood glucose levels associated with increased insulin resistance and GDM development ( Najafi et al, 2020 ). An increasing number of epidemiological studies have examined the relationship between air pollution exposure and the risk of GDM ( Choe et al, 2019 ; Choe et al, 2018 ; Fleisch et al, 2014 ; Fleisch et al, 2016 ; Hu et al, 2015 ; Jo et al, 2019b ; Malmqvist et al, 2013 ; Padula et al, 2019 ; Pan et al, 2017 ; Pedersen et al, 2017 ; Robledo et al, 2015 ; Shen et al, 2017 ; Yu et al, 2020 ; Zhang, et al, 2020a ; Zheng et al, 2020 ), although conclusions are inconsistent regarding the effects of different air pollutants and exposure windows.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we identified that exposure to PM 10 during the 6–11 weeks prior to conception was significantly inversely associated with epigenetic aging at birth. Exposure to PM during preconception has been linked to gestational diabetes mellitus, inflammation during pregnancy, and fetal growth ( Robledo et al, 2015 ; Nachman et al, 2016 ; Najafi et al, 2020 ), suggesting that preconception exposures may affect the growth and development of the placenta and the fetus. Findings from a Chinese study using weekly DLMs showed that exposure to PM 2.5 during the 1–9 weeks prior to conception was associated with fetal undergrowth ( Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the most articles pointed out that exposure to air pollution (through PM 2.5 [98-100, 105, 107, 118-121], PM 10 [98,100,119,121], PM 1 [121], BC [98], NO 2 [119], CO [119], SO 2 [100]) was able to increase blood glucose levels in pregnant women. In n = 7 of n = 9 studies, air pollution was significantly associated (p < 0.05 [98,99,105,119,120], p < 0.01 [107,121]) with elevated fasting blood glucose concentrations. The remaining n = 2 studies by Fleisch et al (n = 2.093) [118] and Lin et al…”
Section: Air Pollution and Glycemic Outcomes (N = 9)mentioning
confidence: 99%